Serological monitoring of avian influenza and Newcastle disease in the Russian Federation in 2020 - M. A. Kulagina; M. A. Volkova; Ir. A. Chvala; O. S. Osipova; P. S. Yaroslavtseva; D. B. Andreychuk; I. A. Chvala (Ветеринария сегодня)
Within the framework of the Rosselkhoznadzor measures aimed at control of highly dangerous  diseases and development of timely recommendations for disease prevention and control, 36,986 serum samples to be tested for the presence of avian influenza virus antibodies and 30,325 serum samples to be tested for the presence of Newcastle disease virus antibodies were submitted to the FGBI “ARRIAH” Reference Laboratory for Avian Viral Diseases  in 2020. The samples were collected from domestic, wild and synanthropic birds in 60 Subjects of the Russian Federation. As a result of the laboratory diagnosis, antibodies against type A influenza virus were found in vaccinated chickens from two poultry farms in the Primorsky Krai. Typing of sample sera using hemagglutination inhibition test showed that the detected antibodies were specific to the haemagglutinin subtype of the vaccine antigen  (A/H9). Antibodies to the H9 subtype  avian influenza  virus were detected in sera of non-vaccinated geese from two poultry farms in the Kurgan Oblast and from one poultry farm in the Republic of Bashkortostan. As for the  backyards where  scheduled  vaccination  against  avian influenza  A/H5 is carried out, a low level of immunity  was seen in the Republics of Adygea and Chechnya (0 and 15%, respectively), while a high immunity level was observed in the Rostov Oblast (74%). High seroprevalence  of Newcastle disease virus was found in adult poultry in indoor industrial farms, which was associated with mass vaccination against the disease. In broiler chickens, post-vaccination antibodies were observed, on average, in 44% of the tested sera samples. The antibodies  against  Newcastle  disease  virus and avian influenza  virus subtype  H5 detected in wild and synanthropic birds indicate the circulation of these viruses in the Russian Federation. The insufficient level of post-vaccination antibodies suggests that the risk of epidemic among poultry in industrial poultry farms and backyards remains.